Macroeconomic determinants of fiscal policy in East Africa: a panel causality analysis - Mawejje, Joseph (2022)
Purpose: This study investigates the dynamic causality linkages between fiscal deficits and selected macroeconomic indicators in a panel of five East African Community countries. Design/methodology/approach: The research design is based on panel cointegration tests, panel cross-section dependence tests, panel error correction-based Granger causality tests and panel impulse response functions. Findings: Results show that there is long-run feedback causality among fiscal deficits and each of the variables include gross domestic product (GDP) growth, current account balance, interest rates, inflation, grants and debt service. Short-run Granger causality dynamics indicate that there is feedback causality between fiscal deficits and GDP growth; no causality between fiscal deficits and inflation; no causality between fiscal deficits and current account; no causality between fiscal deficits and interest rates; feedback causality between fiscal deficits and grants; and no causality between fiscal deficits and debt service. Impulse response functions show positive and significant impacts of current account balance, inflation and grants; negative and significant impacts of real GDP growth and lending rates; and insignificant effects of debt service. Research limitations/implications: While the study examines the dynamic causality between fiscal deficits and selected macroeconomic indicators in the East African Community, the analysis excludes South Sudan due to significant data limitations. Practical implications: In light of the East African Community's aspirations to achieve convergence on key macroeconomic targets, including the fiscal deficit, this research provides novel insights on fiscal policy determinants and causality dynamics. Social implications: The dynamic relationships between fiscal policy and macroeconomic variables may have social implications for welfare, equitable growth and distribution of resources. Originality/value: With a focus on the East African Community, this paper contributes to the literature on the macroeconomic determinants of fiscal deficits in regional economic communities.